Predictive value of the maternal alpha-fetoprotein variant, L2, during the first trimester of pregnancy screening for fetal trisomy 21, trisomy 18, and neural tube defects - Yiming Chen; Wenwen Ning; Caihe Wen; Linyuan Gu; Xuelian Chu (BMC Pregnancy and Childbirth)
Abstract Background To assess the predictive usefulness of maternal serum alpha fetoprotein variant L2 (AFP-L2) for fetal trisomy 21, trisomy 18, and neural tube abnormalities (NTDs) in early pregnancy screening. Methods This retrospective case-control study including 155 fetuses diagnosed with trisomy 21 (n = 83), trisomy 18 (n = 21), and NTDs (n = 51). There are 265 pregnant women with normal development of their fetuses who were chosen at random and included in the control group. The receiver operating characteristic curve was used to determine the optimal screening cut-off value and the area under the curve (AUC). Results The maternal serum AFP-L2 levels in the first trimester of pregnancies with trisomy 21, trisomy 18, and NTD fetuses were higher than the control group [6.64 (4.56–8.09) ng/mL, 6.17 (3.96–8.37) ng/mL, and 6.87(5.29–8.68) ng/mL vs. 3.71 (2.71–4.64) ng/mL], respectively; all P < 0.001). The AUCs for maternal serum AFP-L2 levels in the early stages of pregnancy (11–13+6 weeks) for predicting trisomy 21, trisomy 18, and NTDs were 0.831 (95% CI: 0.775–0.886), 0.783 (95% CI: 0.671–0.896), and 0.876 (95% CI: 0.816–0.937), respectively (all P < 0.001). The positive predictive value of AFP-L2 was greater than free beta-subunit of human chorionic gonadotropin (free β-hCG) and pregnancy-associated plasma protein A (PAPP-A) for predicting trisomy 21 and NTDs. The positive predictive value of AFP-L2 + PAPP-A + free β-hCG + (Maternal age + Gestational age + Maternal weight (MGM)) was greater than single markers. For predicting trisomy 18, the positive predictive value of AFP-L2 was somewhat lower than PAPP-A. AFP-L2 + PAPP-A + free β-hCG + MGM had a higher positive predictive value than single markers. Conclusion We report that the maternal serum AFP-L2 level can be used as a prenatal screening marker to predict NTDs in early pregnancy. AFP-L2 was shown to have high specificity in screening for fetuses with trisomy 21, trisomy 18, and NTDs in the first trimester.